Pengaruh Gaya Kepemimpinan, Situasi Kepemimpinan, Iklim Kerja Organisasi, Terhadap Kinerja Karyawan pada PT. Berlina Plastik Pandaan. - Hariyanto, Hariyanto (Akutansi Bisnis & Manajemen ( ABM ), 2018)
Nowadays, the relationship between leader and subordinates is very decisive work climate organization, with a good work organization climate then the production process becomes smooth, sales targets are met so that corporate goals can be achieved. Sample In this is the employees of PT. Berlina Plastik Pandaan. The analysis method is path analysis. The results of his research are: (1) The change of leadership style (X1) has a positive and significant effect on the organizational climate change cluster (Y1). the leadership situation (X2) has a positive and significant effect on the organizational climate change (Y1). indirect influence between the variables of leadership style (X1), leadership situation (X2), on employee performance variable (Y2) through the influence of organizational climate (Y1), it can be concluded that: coefficient path calculation indirect influence, style of leadership (X1) on employee performance (Y2) through organizational climate change cluster (Y1).